The persistent impact of drought stress on the resilience of summer maize - Jing, Lanshu; Weng, Baisha; Yan, Denghua; Zhang, Shanjun; Bi, Wuxia; Yan, Siying (Frontiers in Plant Science, 2023)
Crop resilience refers to the adaptive ability of crops to resist drought at a certain level. Currently, most of the research focuses on the changes in root or photosynthesis traits of crops after drought and rehydration. Still, the persistence effect (drought period (T2) - rehydration period (T3) - harvest period (T4)) of drought stress on crops and quantitative estimation of resilience is still unclear. Field experiments were conducted in this study to determine the persistence effects on above-ground and below-ground growth indicators of summer maize at different levels and durations of drought. Next, an evaluation method for integrated resilience of summer maize was proposed, and a quantitative assessment of integrated resilience was made by Principal Component Analysis (PCA) and resilience index calculation. The results showed that the resilience of summer maize decreased with increasing drought levels, which persisted until harvest. Although summer maize resilience was strong after rewatering under light drought (DR1), declined after sustained rewatering. At the same time, production had decreased. However, a specific drought duration could improve the resilience of summer maize under light drought conditions. In particular, leaf biomass and root growth in the 30-50 cm layer could be enhanced under long duration light drought (LDR1), thus improving summer maize resilience and yield. Thus, under water shortage conditions, a certain level and duration drought could improve the resilience and yield of summer maize, which would persist until harvest. Clarifying the persistent effects on the growth indicators of summer maize and quantitatively evaluating the resilience of summer maize could improve agricultural food production and water use efficiency.